Is High Intensity Interval Training (HIIT) a feasible method for improving anthropomorphic and cardiometabolic parameters in preschool children? - Jose Carlos Cabrera Linares; Pedro Ángel Latorre Román; Juan Antonio Párraga Montilla; Cristian Martínez Salazar; José Miguel Espinoza Silva (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: High Intensity Interval Training has showed to be an effective method to improve physical fitness and reduce the risk of obesity in adults. However, these effects have not been studied in the preschool population. Objective: The aim of this study was to determine the effects of a long-term High Intensity Interval Training (HIIT) program on anthropomorphic and cardiometabolic variables in preschool children with overweight and obesity. Methods: A total of 349 (164 boys and 185 girls) preschool children (age: 4.38 ± 0.62 years) participated in the study. All the participants completed a 28-week intervention based on HIIT (2 sessions/week), carried out during physical education classes at their schools. Anthropomorphic variables (body mass index, waist circumference, body fat, ∑4 skinfold fat), cardiometabolic variables (blood pressure, resting heart rate, cardiorespiratory fitness), and cardiometabolic risk were measured. Results: After intervention program, significant differences were found in ∑4 skinfold fat, body fat, blood pressure, resting heart rate, and cardiorespiratory fitness. Conclusion: 28-week HIIT training program can reduce cardiometabolic risk and improve cardiorespiratory fitness in preschool children with overweight and obesity regardless of sex.